2017
DOI: 10.1073/pnas.1621490114
|View full text |Cite
|
Sign up to set email alerts
|

The molecular dynamics of long noncoding RNA control of transcription in PTEN and its pseudogene

Abstract: RNA has been found to interact with chromatin and modulate gene transcription. In human cells, little is known about how long noncoding RNAs (lncRNAs) interact with target loci in the context of chromatin. We find here, using the phosphatase and tensin homolog (PTEN) pseudogene as a model system, that antisense lncRNAs interact first with a 5′ UTR-containing promoter-spanning transcript, which is then followed by the recruitment of DNA methyltransferase 3a (DNMT3a), ultimately resulting in the transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…ATP is a required substrate for serine/threonine kinase (ATM) phosphorylation of histones (Banerjee, Bennion, Goldberg, & Allen, 1991), which is removed by protein serine/threonine phosphatases (PSPs) 2013). Additionally, lncRNAs can act as sRNA sponges and stabilize mRNA Lister et al, 2017). As previously stated, lncRNA can also guide nucleosome remodeling proteins to targeted genomic regions (Tang et al, 2017).…”
Section: Rna-mediated Chromatin Regulationmentioning
confidence: 91%
See 1 more Smart Citation
“…ATP is a required substrate for serine/threonine kinase (ATM) phosphorylation of histones (Banerjee, Bennion, Goldberg, & Allen, 1991), which is removed by protein serine/threonine phosphatases (PSPs) 2013). Additionally, lncRNAs can act as sRNA sponges and stabilize mRNA Lister et al, 2017). As previously stated, lncRNA can also guide nucleosome remodeling proteins to targeted genomic regions (Tang et al, 2017).…”
Section: Rna-mediated Chromatin Regulationmentioning
confidence: 91%
“…LncRNAs can guide both histones modifying proteins and DNA methyltransferases to targeted sites on the chromosome, which can give these proteins loci specificity (O’Leary et al, 2017) (reviewed in (Mercer & Mattick, 2013)). Additionally, lncRNAs can act as sRNA sponges and stabilize mRNA (Du et al, 2016; Lister et al, 2017). As previously stated, lncRNA can also guide nucleosome remodelling proteins to targeted genomic regions (Y.…”
Section: Chromatin and Gene Regulationmentioning
confidence: 99%
“…PTENP1 asRNA α binds the PTEN promoter, and epigenetically downregulates PTEN transcription by the recruitment of DNMT3a and Enhancer of zeste homolog 2 (EZH2) to enhance the methylation of PTEN promoter. PTENP1 asRNA α knockdown induces cell cycle arrest and sensitizes cells to doxorubicin, suggesting the biological function for the PTENP1 asRNAs [ 133 , 136 ].…”
Section: Lncrnas Modulate Pten Expression Indirectlymentioning
confidence: 99%
“…Most of human non-coding RNA (ncRNA) transcripts do not code for protein products, but an increasing number of ncRNAs are identi ed to be functional and important in biological or pathological processes [1]. Accumulated evidence suggested that abnormal expression of lncRNAs is often associated with disease pathology especially tumors through microRNA or protein function regulation [2]. Several types of lncRNAs are identi ed as modulating RNAs which possess orchestrated functions involved in the control of genome dynamics, cell biology, and tumor developmental programming [3][4][5].…”
Section: Introductionmentioning
confidence: 99%